Elite Skill and Concussion - Mokri, Eric (Revue YOUR Review (York Online Undergraduate Research), 2022)
It is commonly known that elite athletes in the sport of ice hockey have superior eye-hand coordination and visuomotor skill allowing them to perform at the highest level in their sport when compared to the non-elite population. Previous research has identified a protective motor skill reserve in asymptomatic elite athletes with a history of concussion. This study sought to explore the possibility of lingering visuomotor effects in elite asymptomatic athletes with concussion history. This study sampled male NHL draft prospects and male Kinesiology & Health Science students at York University (Toronto) to examine their visuomotor skills when learning to perform a novel motor learning task. Haptic robotic equipment was used to create a virtual environment allowing participants to navigate the movement tracer around obstacles in the x, y, and z planes of motion. This study supports the findings that the suspected impairments in visuomotor skills are not apparent between elite athletes with and without concussion history when analyzing key performances measures outlined to participants as goals for the task: fastest time to complete the task, and the number of obstacles hit. When analyzing the progression in performance between the three groups studied, it was found that the elite and non-elite groups having no concussion history demonstrated similar improvement outcomes over the course of the ten trials when visuomotor skill was self-controlled by each participants’ motor skills. The elite group with concussion history displayed variable and inconsistent performance through the progression of their consecutive trials at the novel motor learning task.